Paintings as Objects of Discourse Analysis: Two Case Studies - Łuczkiewicz, Magdalena (Respectus Philologicus, 2012)
This article analyses paintings as texts, and examines two paintings visually from different perspectives in order to understand the messages they provide to the audience. Both paintings were created by the Polish painter Zbigniew Maciej Dowgiałło, and present the time of Martial Law in Poland (1981–1983). The article describes the social and political events that took place in communist Poland before and during the imposition of Martial Law. The intention of setting the historical background is to make the time of Martial Law more realistic to the reader. The analysis is presented in the form of individual case studies of each work of art, making use of certain discourse categories (in particular, with the help of the categories of colour, line, character, disposition, opposition and intertextuality). Each category enriches the process of the reconstruction of the content of the text presented in these paintings. It was determined that colour is symbolic in the analysed pictures, serving to bring out emotional value through a variety of associations. It is expressive in form. It was found that varied types of lines are used, not only to frame shapes but also to express emotions. The characters found in the analysed pictures belong to completely different realities, the unreal world (uncommon animals) and the real world (figures of three men). The reconstruction of the unreal world is based on identifying and decoding the artistic visions of the artist, whose painting inspires the imagination and fascinates the viewer. The reconstruction of the content of the painting The Wujek Mine is dependent on certain historical facts. Without some knowledge of the time of Martial Law, reconstruction would be incomplete. The category of intertextuality proves that some other painters and writers have also dealt with the ideas discussed in the analysed paintings. The titles of both paintings are of an informative character and present the source of inspiration. The article concludes that by regarding paintings as texts, it can be seen that the artist sends numerous ideas and content messages to the audience.
Keywords: painting as discourse; discourse picture of the world; discourse picture of viewer response; reconstruction; perspectives of understanding discourse